Procedure For Protecting Citizens In Emergency Situations - Kurbanova Nilufar Ravshanbekovna (Genius Journals, 2024)
In this article described the systematic work carried out today in our country in connection with the protection of the population and territories in emergency situations, their positive aspects, as well as theoretical knowledge of how the population should behave in the event of emergency situations.
Keywords: Emergency situation; civil protection; country system